Local knowledge in inclusive education: a systematic literature review - Ady Dharma, Dwitya Sobat; Mumpuniarti, Mumpuniarti; Efianingrum, Ariefa; Syamsi, Ibnu (International Journal of Evaluation and Research in Education (IJERE), 2025)
This article presents a comprehensive literature review on the role of local knowledge in inclusive education. Employing a systematic review methodology, the study involved goal setting, article selection through abstract and keyword analysis, thorough reading, data abstraction, and subsequent analysis using Publish or Perish 8, Mendeley, and VOSviewer. The review focused on articles published in Scopus-indexed journals between 2020 and 2023. Initial searches identified 259 articles, which were refined to 68 based on their relevance to the research questions. The analysis of these 68 articles revealed three principal findings: i) the diversity of local knowledge in the implementation of inclusive education; ii) global support for integrating local knowledge within inclusive education frameworks; and iii) strategies for incorporating local knowledge into educational practices. These findings underscore the potential of local knowledge to enhance inclusive education through culturally relevant and contextually sensitive approaches, fostering more holistic and responsive educational practices. The review emphasizes the necessity of adapting educational strategies to local contexts to better meet the needs of diverse student populations. It advocates for further research to explore local knowledge in greater depth, aiming to develop more effective and contextually appropriate strategies to improve inclusivity and responsiveness in education globally.